2013
DOI: 10.1007/s00234-013-1208-z
|View full text |Cite
|
Sign up to set email alerts
|

Extension MRI is clinically useful in cervical myelopathy

Abstract: This is the first study to demonstrate added clinical value utilising extension MRI. In this cohort of difficult patients, when there was no T2 signal change in the cord, the presence of clinical myelopathy could only be predicted by utilising the data from extension imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…In previous work, the angle was measured as the difference in vertebrae angles at C2 and C7. 9,10 The angle between these 2 vertebrae is calculated by drawing a line parallel to the posterior edge of the vertebral body, which runs parallel to the spinal cord, and calculating the angle between those 2 lines. The far right artist's illustration depicts segmental rootlets and the formation of a spinal nerve root that emerges from the intervertebral foramen.…”
Section: Does Patient Positioning Within the Mr Imaging Environment Ementioning
confidence: 99%
“…In previous work, the angle was measured as the difference in vertebrae angles at C2 and C7. 9,10 The angle between these 2 vertebrae is calculated by drawing a line parallel to the posterior edge of the vertebral body, which runs parallel to the spinal cord, and calculating the angle between those 2 lines. The far right artist's illustration depicts segmental rootlets and the formation of a spinal nerve root that emerges from the intervertebral foramen.…”
Section: Does Patient Positioning Within the Mr Imaging Environment Ementioning
confidence: 99%
“…Anatomical characteristics may influence biomechanics of the spine [12,26]. However, the Pavlov ratios and the SAC measurements did not reveal any distinct alterations in spinal canal diameter during cervical spine extension.…”
Section: Discussionmentioning
confidence: 78%
“…Flexion-extension MRI techniques have been described in multiple studies (24) and it has been demonstrated that this technique may be helpful in the decision making for the surgical treatment of cervical spine myelopathy (22). Extension MRI in particular has been shown to be clinically useful in cervical myelopathy (3,4). These studies, however, involved the use of non-real-time flexion-extension MRI, aided by custom-built positioning sponges and other techniques that are difficult to reproduce and are therefore clinically impractical.…”
Section: Discussionmentioning
confidence: 99%